The biography of King Faisal I from the early period of his life to his building to the first step of the modern Iraqi state (1883-1924) (Journal of the College of Education for Women, 2019)
The environment and the placesthat prince Faisal Bin AL-Husein influenced his childhood ,behaviourand future . his expereence in his early life in leading the battles andarabRevoluionenriched him . inspite of his short periedand harsh experience of leadersmp.he gained an experienencein ruling iraqadter 1921 . The Syrian experiencetaught him how todeal with the strong and establish the government as he beliered in the slogan: independenceis taken not given. He established the consititution and the election . he made a solidbasefeconomy of in his time, Iraq , Iraq be came the country number ( 53) as anindependency country on the third of November 1932 . he died peacefuliy after Iraq'sindepence.